Plasma Contact Activation and Decrease of Factor V Activity on Negatively-Charged Polyelectrolytes - Boffa, M C; Dreyer, B; Pusineri, C (Thrombosis and Haemostasis, 1984)
The effect of negatively-charged polymers, used in some artificial devices, on plasma clotting and kinin systems was studied in vitro using polyelectrolyte complexes.Contact activation was observed as an immediate, transient and surface-dependent phenomenon. After incubation of the plasma with the polymer a small decrease of factor XII activity was noticed, which corresponded to a greater reduction of prekallikrein activity and to a marked kinin release. No significant decrease of factor XII, prekallikrein, HMW kininogen could be detected immunologically. Only the initial contact of the plasma with the polyelectrolyte lead to activation, subsequently the surface became inert.Beside contact activation, factor V activity also decreased in the plasma. The decrease was surface and time-dependent. It was independent of contact factor activation, and appeared to be related to the sulfonated groups of the polymer. If purified factor V was used instead of plasma factor V, inactivation was immediate and not time-dependent suggesting a direct adsorption on the surface. A second incubation of the plasma-contacted polymer with fresh plasma resulted in a further loss of Factor V activity.
Keywords: Negatively-charged polymers; Polyelectrolyte complex; Contact factors; Factor V